Secrets in the cellar : a true story of the Austrian incest case that shocked the world - Glatt, John. (New York : St. Martin's Press, 2009)
A loving father-- a missing daughter-- and the awful truth that lay hidden just below. The true story of the Austrian incest case that shocked the world.
A Nazi childhood -- Starting a family -- "If you scream, I will kill you!" -- Elisabeth -- "The pig will beat us to death one day" -- Escape -- Brief encounter -- Taken -- His second wife -- Children of the cellar -- The foundlings -- Pillar of the community -- A double life -- His underground kingdom -- Losing control -- Into the light -- Freedom -- A reunion -- "It's beyond comprehension" -- "Hey, Satan, come out and play!" -- "The devil himself" -- Under siege -- "I could have killed them all" -- "We, the whole family" -- Frankenstein -- Miracle -- A new start -- Elisabeth speaks.
Keywords: Incest -- Case studies; Child sexual abuse -- Case studies; Imprisonment -- Case studies; Parental kidnapping -- Case studies